REGISTERAL DIFFERENCES AND TYPICAL LINGUISTIC FEATURES OF MANUALS, RECIPES, ADVERTISEMENTS, BROCHURES, AND REGISTRATION FORM: A REGISTER ANALYSIS - Wa Ode Hanafiah (JURNAL ILMU BUDAYA, 2022)
Every genre has its own typical linguistic features to enable them to be different from others. The study reported here discusses the registeral differences and typical linguistics features of five different types of genres. They are manuals, recipes, advertisement, brochures, and registration forms. The study is descriptive qualitative in nature. The data were taken randomly from the five selected genres consisting of words ranging from 350 words to 1000 words as the samples of the study. These then were analyzed utilizing a content-based analysis. The study concluded that certain linguistic items that each of the five selected genre employed provides the genre with their own typical linguistic features. These features enable the given genres to be identifiable and distinctive. These typicality are mostly determined by the main function the given genres play. The functions the genres make them employ certain lexicons and syntactical forms